NAVIGATING THE CHIEF MARKETING OFFICER’S DUAL MANDATE: A STUDY OF TENSIONS BETWEEN ENTREPRENEURIAL INNOVATION AND OPERATIONAL EFFICIENCY - Jajang Jamaludin; Lukmanul Hakim; Dahrul Aman Harahap (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study examines how Chief Marketing Officers (CMOs) balance the competing demands of innovation and operational efficiency within contemporary organizations. Drawing on ambidexterity theory and paradox theory, the research explores how marketing leaders manage exploration–exploitation tensions while maintaining organizational performance. Using a qualitative and conceptual analytical approach, the study identifies key strategies adopted by CMOs, including data-driven decision-making, structural separation, collaborative culture, integrative thinking, and adaptive leadership practices. The findings reveal that effective CMOs do not attempt to eliminate tensions between innovation and efficiency but instead manage them dynamically through flexible leadership and organizational alignment. The study further demonstrates that organizational context, such as supportive culture, flexible structures, and top management support, significantly influences the effectiveness of balancing these dual demands. The results contribute to ambidexterity theory by emphasizing that ambidexterity functions not only as an organizational capability but also as a leadership competency. In addition, the study advances paradox theory by showing that competing objectives can coexist and become sources of strategic advantage when managed effectively. Overall, the research provides important theoretical and practical insights into contemporary marketing leadership and offers a comprehensive framework for understanding how CMOs navigate organizational tensions to achieve sustainable performance and long-term strategic success.